Huntington's Disease, Huntington's Disease Look‐Alikes‎, and Benign Hereditary Chorea: What's New?. Issue 4 (27th January 2016) - Schneider, Susanne A.; Bird, Thomas
Abstract: Background: The differential diagnosis of chorea syndromes is complex. It includes inherited forms, the most common of which is autosomal dominant Huntington's disease (HD). In addition, there are disorders mimicking HD, the so‐called HD‐like (HDL) syndromes. Methods and Results: Here we review main clinical, genetic, and pathophysiological characteristics of HD and the rare HD phenocopies in order to familiarize clinicians with them. Molecular studies have shown that HD phenocopies account for about 1% of suspected HD cases, most commonly due to mutations in C9orf72 (also the main cause of frontotemporal dementia and amyotrophic lateral sclerosis syndromes), TATA box‐binding protein (spinocerebellar ataxia type 17 [SCA17]/HDL4), and JPH3 (HDL2). Systematic screening studies also revealed mutations in PRNP (prion disease), VPS13A (chorea‐acanthocytosis), ATXN8OS‐ATXN8 (SCA8), and FXN (late‐onset Friedreich's Ataxia) in single cases. Further differential diagnoses to consider in patients presenting with a clinical diagnosis consistent with HD, but without the HD expansion, include dentatorubral‐pallidoluysian atrophy and benign hereditary chorea ( TITF1 ), as well as the recently described form of ADCY5 ‐associated neurodegeneration. Lastly, biallelic mutations in RNF216 and FRRS1L have recently been reported as autosomal recessive phenocopies of HD. Conclusion: There is a growing list of genes associated with chorea, yet a substantial percentage of patients remain undiagnosed. It is likely that more genes will be discovered in the future and that the clinical spectrum of the described disorders will broaden.